Aktualisasi Pancasila dan Civil Society Diera Globalisasi - Kamdani Kamdani; Dian Dian; Fachri Abdu Wiguna (Student Research Journal, 2025)
This study employs a descriptive qualitative approach to explore the actualization of Pancasila values in fostering civil society in the globalization era. Literature review serves as the primary method, analyzing data from journals, books, academic articles, and official documents. The study identifies key themes regarding Pancasila's role in politics, law, socio-culture, economy, and education. Findings reveal that implementing Pancasila values strengthens unity, social justice, and tolerance through character education, community participation, and strengthening civil institutions. In the globalization context, Pancasila faces challenges such as radicalism, misinformation, and digital inequality, but also opens opportunities for innovation through information technology, cultural preservation, and e-governance. Civil society plays a pivotal role in integrating Pancasila values with global dynamics to build social harmony and a resilient national identity.